ERCP : the fundamentals - Cotton, Peter B.; Leung, J. W. C. (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley Blackwell, 2015)
Peter Cotton and Joseph Leung have once again assembled many of the world's leading experts in this field to provide clear and concise guidance. There are chapters on "How to do" all of the specific manoeuvers, followed by chapters on "When to do" them (and when not to). Key highlights include the following: -Full coverage of the entire range of both standard and advanced techniques, using a highly practical approach -Strong focus on patient education, safety, and minimizing risks -Twenty-four outstanding procedural videos of the experts performing ERCP, ideal for improving best practice techniques -Over 250 excellent illustrative photos, X rays, and anatomical drawings - "Tips and tricks" and key points throughout to aid rapid understanding -Reference to the latest ASGE, ACG, ASG, and UEGW guidelines throughout New to this second edition are a host of new topics, including simulation training, formal credentialing and certification, wire-guided cannulation techniques, pancreatic stenting, short wire technology, cholangioscopy, plastic versus metal stents, radiofrequency ablation, sphincter manometry, and ERCP in acute pancreatitis. Brought to you by world pioneers in endoscopy, ERCP: The Fundamentals, 2nd Edition, is an essential purchase for gastroenterologists and endoscopists of all levels.
Training and assessment of competence (preparing the endoscopist) / Joseph Leung and Peter B. Cotton -- Preparing the facilities and equipment / Joseph Leung -- The ERCP team and teamwork / Phyllis Malpas -- Patient education and consent / Peter B. Cotton -- Risk assessment and reduction / Joseph Romagnuolo -- Sedation, anesthesia and medications / John J. Vargo II -- Standard devices and techniques (how to do it) / Joseph Leung -- When standard cannulation approaches fail / Sandeep Lakhtakia, Bronte A. Holt and Shyam Varadarajulu -- Intraductal procedures / D. Nageshwar Reddy and Mohan Ramchandani -- Sphincter of Oddi manometry / Evan L. Fogel and Stuart Sherman -- Endoscopic ampullectomy / Michael Bourke -- The radiology of ERCP / Derrick Martin -- ERCP reporting and documentation / Lars Aabakken -- ERCP in acute cholangitis / Wei-Chih Liao and Hsiu-Po Wang -- ERCP peri-cholecystectomy / Paul R. Tarnasky -- Large bile duct stones / Julia McNabb-Baltar and Alan Barkun -- The patient with pain : suspected gall bladder and sphincter dysfunction / Peter B. Cotton -- Benign biliary strictures / John T. Cunningham -- The role of ERCP in pancreatico-biliary malignancies / John G. Lee -- ERCP in acute and recurrent acute pancreatitis / Gregory A. Co -- ERCP in chronic pancreatitis / Wiriyaporn Ridtitid, Evan L. Fogel and Stuart Sherman -- The role of ERCP in complicated pancreatitis / Todd H. Baron -- ERCP in children / Moises Guelrud and Andres Gelrud.
Preceded by: Advanced digestive endoscopy / edited by Peter B. Cotton and Joseph Leung. 2006.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Cholangiopancreatography, Endoscopic Retrograde -- methods; Biliary Tract Diseases -- diagnosis; Biliary Tract Diseases -- surgery; Pancreatic Diseases -- diagnosis; Pancreatic Diseases -- surgery; Biliary tract -- Diseases -- Diagnosis; Biliary tract -- Diseases -- Diagnosis; MEDICAL / Gastroenterology; Medical; Electronic books; Electronic books